Preventing exclusions - Abdelnoor, Adam. (USA : Heinemann educational, 1999)
Using real-life case studies, this book helps to identify potential problem pupils early on. The author suggest actions that can be taken to help prevent the child from being excluded.
Includes bibliography reference and index.
Keywords: Student suspension -- Great Britain; Student suspension -- Case studies -- Great Britain